The ability of natural / synthetic fibers compound for ballistic impedance: A review - Saion, Mohamad Pazlin bin; M. Y., Yuhazri; M. H., Amirhafizan (Jurnal Teknik Mesin (Journal Of Mechanical Engineering), 2022)
Mechanical characteristics of the laminated composite crafted from fabric type reinforcement perhaps inspired via the usage of the weaving method and reinforcement agent due to the constructional parameter of each layer. As a result, the research on the arrangement configuration between bio composite fiber and synthetic fiber for the composite shape is proposed in the direction of enhancing biodiversity and physical characteristics of the composite structure. Substitute for natural fiber in synthetic fiber composite works has the excessive capacity to be explored scientifically. This evaluates focused on the concept and essential of bio composite and the synthetic composite fabric positioned over the years from the previous studies of the preliminary researches. The sorts and features of matrix and fiber filler reinforcement materials in composites also are discussed. The main findings in this assessment show that the centre of composite relies on the weave styles and the roles of interply and intraply lamination. Therefore, the state-of-the-art intraply for synthetic fiber and biocomposite fiber in a composite shape is anticipated performing higher in the issue of mechanical energy in particular within the application of ballistic resistance, besides decreased dependency on artificial fiber. It will ultimately suggest the excellent weave sample designs in the useful combination shape of natural and synthetic fibers embedded with polymers. The statistical results are comparing with the experimental parameters available inside the literature review. These review ambitions in explaining approximately the studies and evolution within the enhancement of characteristic fibers reinforced polymer composites in ballistic resistance use. This paper goes over the body armour profitable and present advancement materials, structure and development procedures included and related works on upgrading ballistic energy captivation and upgrading the mechanical tenacity for high impact resistance applications.